A Rapid, Semi-Quantitative Assay to Screen for Modulators of Alpha-Synuclein Oligomerization Ex vivo - Delenclos, Marion; Trendafilova, Teodora; Jones, Daryl R.; Moussaud, Simon; Baine, Ann-Marie; Yue, Mei; Hirst, Warren D.; McLean, Pamela J. (Frontiers in Neuroscience, 2016)
Alpha synuclein (αsyn) aggregates are associated with the pathogenesis of Parkinson’s disease and others related disorders. Although modulation of αsyn aggregation is an attractive therapeutic target, new powerful methodologies are desperately needed to facilitate in vivo screening of novel therapeutics. Here we describe an in vivo rodent model with the unique ability to rapidly track αsyn-αsyn interactions and thus oligomerization using a bioluminescent protein complementation strategy that monitors spatial and temporal αsyn oligomerization ex vivo. We find that αsyn forms oligomers in vivo as early as 1 week after stereotactic AAV injection into rat substantia nigra. Strikingly, although abundant αsyn expression is also detected in striatum at one week, no αsyn oligomers are detected at this time point. By 4 weeks, oligomerization of αsyn is detected in both striatum and substantia nigra homogenates. Moreover, in a proof-of-principle experiment, the effect of a previously described Hsp90 inhibitor known to prevent αsyn oligomer formation, demonstrates the utility of this rapid and sensitive animal model to monitor αsyn oligomerization status in the rat brain.